Pendidikan Islam Sebagai Grand Design Pendidikan Karakter - Suharmoko Suharmoko (Al-Riwayah : Jurnal Kependidikan, 2017)
Character education can be defined as the process of planting the essential values in children through a series of learning activities and assistance so that the students as individuals are able to understand, experience, and integrate values into core values in education into her personality. By placing the character education within the framework of the dynamics and dialectics of the individual establishment, the men and women educators are expected to increasingly be aware of the importance of education as a means of forming the character code of conduct, moral formation and enrichment of individual value by providing space for exemplary figure and creating an environment conducive to the growth process, such as comfort and security of self-development environment that helps each other in overall dimensions (technical, intellectual, psychological, moral, social, aesthetic, and religious).